Full dynamic resolution low lower DA-Converters for flat panel displays - C. Saas; J. Franke; J. A. Nossek (Advances in Radio Science, 2006)
It has been shown that stepwise charging can reduce the power dissipated in the source drivers of a flat panel display. However the solution presented only provided a dynamic resolution of 3 bits which is not sufficient for obtaining a full color resolution display. In this work a further development of the basic idea is presented. The stepwise charging is increased to 4 bits and supplemented by a current source to provide an output signal which represents an 8 bit value with sufficient accuracy. Within this work the application is an AM-OLED flat panel display, but the concept can easily be applied to other display technologies like TFT-LCD as well.